(3fXe eSGfOI GdbQGQGJs - (3SYO ZGdH jGSjf(B, (3GdJcQjJjs ((3YeGf(B:s (3OGQ GdefGgL(B,s, 2000)
(3JMdjd fXe eSGfOI GdbQGQGJ(B- (3gjcd fXe eSGfOI GdbQGQGJ(B- (3CfhGY CfXeI eSGfOI GdbQGQGJ(B- (3fXe OYe GdPcj ddbQGQGJ GdGYeGd GdEdcJQhfjI(B- (3JUeje fXe eSGfOI GdbQGQGJs
Keywords: (3EJNGP GdbQGQs; (3fXe GdeYdheGJ(B- (3GdeDSSI GdeeJOI s